2015
DOI: 10.5194/acp-15-3193-2015
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of isotopic composition in water vapor over western Africa and its relationship to ENSO

Abstract: Abstract. This study was performed to examine the relationship between isotopic composition in near-surface vapor (δ 18 O v ) over western Africa during the monsoon season and El Niño-Southern Oscillation (ENSO) activity using the Isotope-incorporated Global Spectral Model. The model was evaluated using a satellite and in situ observations at daily to interannual timescales. The model provided an accurate simulation of the spatial pattern and seasonal and interannual variations of isotopic composition in colum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
(91 reference statements)
1
28
0
Order By: Relevance
“…2a and f). Okazaki et al (2015) also found that the main driver of the more depleted δ 18 O v from Niamey was a larger amount of precipitation at the Guinea coast.…”
Section: The Effects Of Meteorological and Environmental Factors On δmentioning
confidence: 90%
“…2a and f). Okazaki et al (2015) also found that the main driver of the more depleted δ 18 O v from Niamey was a larger amount of precipitation at the Guinea coast.…”
Section: The Effects Of Meteorological and Environmental Factors On δmentioning
confidence: 90%
“…Nevertheless, because of the integrated nature of δD, we show that some information can be derived from the δD signature of air parcels coming from the desert. Former studies have already been dedicated to the interpretation of isotopic variations observed in precipitation and in water vapour in West Africa (Frankenberg et al, 2009;Risi et al, 2010;Okazaki et al, 2015) by combining models with observations, but solely focusing on the role of convection. From in situ measurements at Izana, have shown that different air mass pathways could be detected in H 2 O-δD pair distribution.…”
mentioning
confidence: 99%
“…The performance of IsoGSM in producing atmospheric isotopic variability data has been evaluated in several previous studies. Simulated IsoGSM data show good agreement with observed isotopic spatiotemporal variability, suggesting that the model can reproduce the dynamics of atmospheric moisture transport satisfactorily (Berkelhammer et al 2012;Ishizaki et al 2012;Nakamura et al 2014;Okazaki et al 2015). In this study, the simulated stable isotope ratios in the precipitation data over the JAMSTEC and GNIP stations were correlated significantly with the observations (significance exceeding 95 %); the root mean square errors (RMSEs) were 1.71-2.98 ‰ for δ 18 O, while the standard deviations (σ) of the observed isotopes were 1.73-3.01 ‰.…”
Section: Observationsmentioning
confidence: 67%